2015
DOI: 10.1038/ncomms8736
|View full text |Cite|
|
Sign up to set email alerts
|

STAT3 regulated ARF expression suppresses prostate cancer metastasis

Abstract: Prostate cancer (PCa) is the most prevalent cancer in men. Hyperactive STAT3 is thought to be oncogenic in PCa. However, targeting of the IL-6/STAT3 axis in PCa patients has failed to provide therapeutic benefit. Here we show that genetic inactivation of Stat3 or IL-6 signalling in a Pten-deficient PCa mouse model accelerates cancer progression leading to metastasis. Mechanistically, we identify p19ARF as a direct Stat3 target. Loss of Stat3 signalling disrupts the ARF–Mdm2–p53 tumour suppressor axis bypassing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
161
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(174 citation statements)
references
References 65 publications
13
161
0
Order By: Relevance
“…STAT3 acts as signal messenger and TF and participates in normal cellular responses to cytokines and growth factors specifically to IL6 . STAT3 overexpression is thought to be oncogenic in prostate cancer [3,45]. Based on this observation IL-6 / STAT3 signaling inactivation was proposed as possible treatment for prostate cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…STAT3 acts as signal messenger and TF and participates in normal cellular responses to cytokines and growth factors specifically to IL6 . STAT3 overexpression is thought to be oncogenic in prostate cancer [3,45]. Based on this observation IL-6 / STAT3 signaling inactivation was proposed as possible treatment for prostate cancer.…”
Section: Resultsmentioning
confidence: 99%
“…There are a number of genes involved in prostate cancer progression, which have been reported to be downregulated in some studies and overexpressed in other studies (e.g. STAT3 ) [2,3]. A large number of studies are based on a reductionist approach to confirm the role of one or another gene or signaling pathway as a key player in prostate cancer metastasis [48].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, STAT3 promotes cellular senescence by upregulating p19 in prostate cancer (30), and it will be interesting to assess whether this mechanism is conserved also in MuSCs. These findings suggest that pharmacological manipulation of STAT3 could provide therapeutic approaches for muscle maintenance and repair.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, anti-IL-6 agents (e.g., siltuximab) or JAK/STAT3 inhibitors were not only ineffective in metastatic PCa, but also enhanced expression of proliferation markers in PCa patients 6 or in vivo xenografts. 8 LNCaP cells/xenografts are most frequently used in PCa research and contrasting results were reported in vitro and in vivo after IL-6 treatment. 4,7 For this reason, we took advantage of a prostate epithelial-specific loss of Pten transgenic mouse model and in addition deleted Stat3 or IL-6.…”
mentioning
confidence: 99%
“…One should keep in mind that the cells initially inhibited by IL-6 may become predisposed to loss of tumor protein (TP53, best known as p53), accompanied by metastatic progression. 8 The results of the study by Pencik and associates should motivate translational researchers to investigate expression of several downstream targets of STAT3-ARF in PCa. The studies should also be extended to tumor-initiating cells in which activation of STAT3 by IL-6 is clearly demonstrated.…”
mentioning
confidence: 99%